The Use of TASC (Telenursing After Stroke Care) to Improve Family Preparedness to Care for Stroke Patients - Siti Zuraida Muhsinin; Musniati Musniati; Dewi Komala Sari; Aura Athiyah Anargia (Indonesian Journal of Global Health Research, 2025)
Stroke is a non-communicable disease with a high incidence in Indonesia and is a major cause of disability and death. Families play an important role in post-stroke patient care at home but often feel unprepared due to limited knowledge, skills, and support. The use of technology through Telenursing After Stroke Care (TASC) is expected to improve family preparedness in caring for stroke patients at home. This study aims to analyze the effect of TASC on family preparedness in caring for stroke patients at home. The study used a pre-experimental design with a one-group pre-test post-test approach. The sample consisted of 35 families of stroke patients at RSUD Kota Mataram, selected using a total sampling technique. The TASC intervention was carried out for 1 month with two weekly sessions, including education on stroke concepts, family roles, basic home care, complication prevention, stress management, and daily care planning. The Preparedness for Caregiving Scale (PCS) was used as the instrument, The results of the validity and reliability test of this instrument, the validity test with Pearson product moment has a value of more than 0.320 and the results of the reliability test with Cronbach's alpha have a value of 0.9333. Data were analyzed using a paired t-test. The average family preparedness score before the intervention was 17.29 (SD = 3.47) and increased to 23.23 (SD = 4.35) after the intervention. The paired t-test showed a p-value of 0.000 (p < 0.05), indicating a significant difference in family preparedness after the TASC intervention. The use of TASC is effective in improving family preparedness in caring for stroke patients at home. This intervention can be an appropriate strategy to support discharge planning, prevent complications, and reduce rehospitalization rates.